Music Expertise and Gender Differences in Verbal and Visual Divergent Thinking. A Behavioral Study. Issue 3 (3rd July 2021) - Diaz Abrahan, Verónika; Sarli, Leticia; Shifres, Favio; Justel, Nadia
ABSTRACT: Research on creativity is a field of great relevance since it studies our capacity to create, the root of all innovation and problem solving. Some factors, like personality, motivation and artistic knowledge, are known to influence creativity. The aim of this study was to investigate the influence of music expertise and gender on creativity and the interaction between these factors. One hundred and fifty-eight participants, aged between 18 and 50, were involved in the study. Eighty-seven of them were musicians (56 male and 31 female) and 71 non-musicians (30 male and 41 female). To evaluate creativity, two tasks, one verbal and one visual, were used, each lasting 2 minutes. Fluency, Flexibility, Originality, Elaboration, and General Creativity were the creative domains under evaluation. The results showed statistically significant differences in music expertise and, to a lesser extent, in gender, especially in the verbal task. Music expertise had a positive impact on creative performance, and women were found to be more creative in the verbal domain than men. This research extends previous work on the influence of biological and environmental factors on creativity.